ECOLOGY, PRODUCTION AND LIVING: RESEARCH ON THE PLANNING AND CONSTRUCTION OF RURAL FEATURES BASED ON THE EPL SYSTEM - C. C. Xu; Z. Y. Chai; Y. C. Gao (International Association of Lowland Technology, 2013)
Rural planning and construction carries influential natural, economic, social and cultular connotation. The problem of rural fetures deficiency has prevailed and construction process in Zhejiang Province in China, the article presented a way of recognizing different rural landscape styles, and put forward guiding ideas and spatial strategies for the planning and construction of rural features, from the perspective of ecological system, production system, and living system (namely